Petar & Liza - Sekulić-Struja, Miroslav 1976- (Fantagraphics, 2024)
"When Petar returns home to civilian life after his two-year conscription in the ex-Yugoslavian army, he finds himself adrift. Even amidst the most raucous, late-night parties, he feels detached from it all, like a ghost haunting the living. But a serendipitous encounter with Liza, a dancer with a joie de vivre about her, brings a flood of vibrant color into his gray life. Their lyrical romance forms an oasis in a bleak world, until his inner demons start to reveal themselves"--
Keywords: Yugoslav War, 1991-1995 / Comic books, strips, etc; Orphans / Comic books, strips, etc; Poets / Comic books, strips, etc; Dancers / Comic books, strips, etc; Man-woman relationships / Comic books, strips, etc; Comic books, strips, etc; Croatia / https://id.oclc.org/worldcat/entity/E39PBJqBvTfkJyB3h3MYHMm8G3; Graphic novels; Comics (Graphic works); Bandes dessinées; Comic